The Effect of Adolescent Therapeutic Group Therapy and Cognitive Behavioral Therapy in the Occurrence of Depression - Andalasari, Niken; Keliat, Budi Anna; Putri, Yossie Susanti Eka (Jurnal Kesehatan, 2024)
Adolescents are tasked with developing identity vs. role confusion, where the search for identity will shape the individual's character. There has been an increase in the use of social media among adolescents, causing an increase in the number of depression in adolescents. The need for promotive and preventive efforts to prevent depression in adolescents. This study aims to determine the effect of therapeutic group therapy and cognitive behavioral therapy in preventing depression in adolescent social media users. This study was conducted on 70 students aged 15-18 years old using a purposive sampling technique according to inclusion and exclusion criteria. This study uses a quasi-experimental pre-post-test design with intervention and control groups. The intervention group was given therapeutic and cognitive behavioral therapy, and the control group was given therapeutic group therapy without cognitive behavioral therapy. The results of this study indicate a significant effect on the control group. The combination of therapeutic group therapy therapy and cognitive behavioral therapy can be recommended as a therapy for reducing depression in adolescent social media users.